Characteristics of Islam Nusantara: Manifestation of Walisongo's Moderatism in Contemporary Context - Ratu Qhaylla Zasqyah Chandra; Rensa Septiansyah; Nurjaya (Lentera Peradaban: Journal on Islamic Studies, 2025)
This paper aims to find out the character of Islam Nusantara, as a manifestation of the existence of moderate Islam that was taught by the Walisongo and religious figures to this day. The historical phenomenology is employed to understand Islam Nusantara. The results of this research showed that Islam in Nusantara has five special characters. First, Islam Nusantara is always in accordance with their contexts. Second, it has a tolerant attitude towards differences. Third, it appreciates traditions that have long existed before. Fourth, it has a progresive attitude towards the progress of time. Fifth, it emancipates